Pemanfaatan Jeruk (Citrus Sinensis) dengan Penambahan Natrium Karbonat (Na₂CO₃) untuk Pembuatan Bio-Baterai - Bramantio, Iqbal; Rusdianasari, Rusdianasari; Aziz Pramito, Akbar Ismi (Jurnal Teknologi, 2025)
The increasing demand for electrical energy due to population growth, urbanization, and technological development requires alternative solutions that are environmentally friendly and sustainable. Conventional batteries generally contain hazardous heavy metals, thus encouraging the development of bio-batteries using natural materials. This study aims to utilize orange (Citrus sinensis) juice as an electrolyte in the fabrication of bio-batteries and to investigate the effect of sodium carbonate (Na₂CO₃) addition on their electrochemical performance. The research was conducted experimentally by preparing electrolyte solutions consisting of orange juice with variations in volume (200–400 mL) and Na₂CO₃ concentration (0.5; 1; and 2 M). Electrodes used were copper (Cu) as cathode and aluminum (Al) as anode, arranged in series within a BioChamber. Parameters measured included pH 5, voltage, current, power, conductivity, and LED lighting duration. The results show that the optimum condition was obtained at 200 mL of orange juice with 0.5 M Na₂CO₃, producing a voltage of 6.45 V, a current of 30.89 mA, a power of 199.24 mW, and LED lighting duration of approximately 356 minutes. Increasing the Na₂CO₃ concentration to 1 M and 2 M decreased the performance due to the excessive alkalinity of the solution. This study demonstrates that orange juice combined with Na₂CO₃ has significant potential as an alternative, environmentally friendly energy source for the development of green energy technologies.